2016
DOI: 10.1539/joh.16-0096-cs
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of rare chronic lipoid pneumonia associated with occupational exposure to paraffin aerosol

Abstract: Objectives: Occupational exposure to paraffin is an infrequent cause of lipoid pneumonia (LP) and related data are scare. We investigated the possible relationship between three rare cases of chronic LP and occupational exposure to paraffin aerosol in an iron foundry. Methods: The three cases of LP and their workplaces were investigated using data from field investigations, air monitoring, pulmonary radiological examinations, cell staining, and lung biopsies. Results: The patients had long-term occupational ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Reanalyses after excluding (113) Lung tissue particles 37 35 Rubin, 1980, Canada (114) Reported history 13 15 Kariman, 1984, USA (115) Reported history 23 0 Prakash, 1987, USA (116) Reported history 34 9 Asamoto, 1995, Japan (117) Reported history 68 15 Goldstein, 1998, USA (118) Reported history 24 50 Kim, 1999, Korea (119) Reported 137Reported history 17 29 Mo, 2016, China (138) Reported history 11 18 Guo, 2017, China (139) Reported history 37 49 Hwang, 2017, Korea 140Reported history 71 48 Definition of abbreviation: USA = United States. All studies are case series except four case-control studies (113,126,133,158) and one national registry (121). "Reported history" refers to occupational or exposure history from the clinical record.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reanalyses after excluding (113) Lung tissue particles 37 35 Rubin, 1980, Canada (114) Reported history 13 15 Kariman, 1984, USA (115) Reported history 23 0 Prakash, 1987, USA (116) Reported history 34 9 Asamoto, 1995, Japan (117) Reported history 68 15 Goldstein, 1998, USA (118) Reported history 24 50 Kim, 1999, Korea (119) Reported 137Reported history 17 29 Mo, 2016, China (138) Reported history 11 18 Guo, 2017, China (139) Reported history 37 49 Hwang, 2017, Korea 140Reported history 71 48 Definition of abbreviation: USA = United States. All studies are case series except four case-control studies (113,126,133,158) and one national registry (121). "Reported history" refers to occupational or exposure history from the clinical record.…”
Section: Discussionmentioning
confidence: 99%
“…Although PAP has a more robust literature relevant to the occupational burden of disease, there are a number of other respiratory syndromes in which occupational associations have been observed in disease outbreaks, in certain work settings, or after suspect exposures (142,(145)(146)(147)(148)(149)(150)(151)(152)(153)(154)(155)(156)(157)(158)(159)(160)(161). Table E2 provides selected examples of these reported associations, which include bronchiolitis and the Overall (I^2 = 99.72%, p = 0.00) All studies had case-control designs, with most by interview-based self-reported exposure assessment (Hubbard exposure by job category).…”
Section: American Thoracic Society Documentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there should be an emphasis on the importance of occupational exposure history in patients with non-resolving pneumonia when lipoid pneumonia is suspected. The occupational history should include information about routine tasks performed during a typical work shift and the use of chemicals such as paraffin (11), diesel (4), petroleum jelly, and cutting mist (1). In some cases, patients have limited knowledge of the substances to which they have been exposed.…”
Section: Discussionmentioning
confidence: 99%
“…It is majorly associated with the use of mineral oils, which are a mixture of inert, longchain, saturated hydrocarbons obtained from petroleum [2]. Occupational exposure to these mineral oils is an uncommon cause of lipoid pneumonia [1][2][3]. Moreover, limited data are available on cases of occupational lipoid pneumonia [2,3].…”
Section: Introductionmentioning
confidence: 99%